NORM INEQUALITIES OF NORM-ATTAINABLE OPERATORS AND THEIR ORTHOGONAL EXTENSIONS - okelo, benard; Ongati, Omolo; Karieko, Obogi Robert (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
We present new norm inequalities of matrices of norm-attainable operators and characterize the maps that act on matrices of these operators. Moreover, we characterize completely bounded norms, give their orthogonal extensions and extensions via norm-convergence in NA(H)-classes.